HUBUNGAN FAKTOR SOSIAL DAN SPIRITUAL DENGAN RISIKO PENYALAHGUNAAN NAPZA PADA REMAJA SMP DAN SMA DI KOTA PALEMBANG 2009 - Jaji Jaji (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
NAPZA is a threat most feel concerned abouts for adolescent in can be more than 100 countries in the world. Indonesia are known from 3,2 million people is user NAPZA. Every year user amount NAPZA increases 1 million people, from 1 million user that increase, known 5,3%among others is student community and student, that means from 100 users NAPZA are existed five student or students as abuse to NAPZA. This research Design uses descriptive analytic method with approach cross sectional. Sampel research amounts to 384 adolescent, intakeprocedure sampel with random proportional stratified sampling, and random simple sampling. This Research uses statistic test Chi Square that bent on to know there is independent variable relation with dependen. Independent Variable its that is: social factor, spiritual, age, gender, and education relates to abuse NAPZA at adolescent in Palembang city. Whereas to know factor the most dominant range from to factors, researcher uses statistic test multivariat that is double logistics regression. Research Result is got there is relation between social and education level adolescent and abuse risk NAPZA, and there is no relation between age, gender, and spiritual with abuse risk NAPZA, and variable the most having an effect on is social variable. Research that conducted give picture that abuse risk NAPZA at adolescent more beriko at high adolescent social, and spiritual adolescent that not support.